A Study on the Synergistic Effects of Hip Capsule Nerve and Stellate Ganglion Block on Postoperative Rehabilitation Outcomes in Elderly Patients Following Total Hip Arthroplasty - Di Liu MMed; Yunzhi Ling MD; Nannan Song MMed; Wentao Dai MMed; Meijun Shen MMed; Congli Zhang MD (Geriatric Orthopaedic Surgery & Rehabilitation, 2025)
Objective The presenting research aimed to assess the clinical results of hip pericapsular nerve group block (PENGB) combined with stellate ganglion block (SGB) on postoperative pain management and early rehabilitation in total hip arthroplasty (THA) patients. Methods There were 50 THA cases at our hospital inluded in the study. Twenty-five patients in the experimental group received general anesthesia combined with PENGB and SGB, while the remaining 25 patients in the control group received conventional general anesthesia. Mean arterial pressure and heart rate were recorded 30 min after the start of surgery and immediately postoperatively. The Numeric Rating Scale (NRS) scores for pain at rest and during movement were recorded at baseline (T0), 30 min (T1), 6 h (T2), 24 h (T3), and 48 h (T4) after the combined block was administered. The Athens Insomnia Scale (AIS) scores were recorded for 2 consecutive days postoperatively. Additionally, the number of analgesic pump presses, the time to first mobilization, patient satisfaction scores, and postoperative complications were documented. Results Compared with the control group, the experimental group exhibited more stable hemodynamics 30 min after the start of the operation and immediately postoperatively ( P < 0.05). At T0, the 2 groups had no significant difference in NRS scores ( P > 0.05). However, from T1 to T4, the experimental group had significantly lower NRS scores at rest and during movement, AIS scores for 2 consecutive days post-surgery, achieved earlier mobilization, shorter hospital stays, and reported higher overall satisfaction with hospitalization, all of which were statistically significant ( P < 0.05). The postoperative complications rate of the 2 groups were similar ( P > 0.05). Conclusion PENGB combined with SGB significantly enhances postoperative pain management, shortens hospital stay, and improves early rehabilitation outcomes in elderly patients undergoing total hip arthroplasty compared to conventional general anesthesia.